Economic indicators in the use of corn seed of normal and protein quality (QPM) in Veracruz - Hernández Salgado, José Hilario; Jaramillo Albuja, José Gabriel; Espinosa Calderón, Alejandro; Peña Olvera, Benjamín Valeriano; Díaz Ruiz, Ramón (Revista Mexicana de Ciencias Agrícolas, 2018)
Corn is one of the most outstanding crops of the Mexican Republic, because it is an important part of the Mexican diet, as well as having a strong social and cultural connotation in the country; however, the yields of this cereal are low due to the fact that, among other factors, the use of improved seed is scarce in the state of Veracruz. It has been estimated that the use of improved seed is 22% with an average yield of 2.2 t ha-1. This paper analyzes the impact of productivity and estimates maximum prices of corn seed that farmers would be willing to pay for corn hybrids that were evaluated in the localities of Tlachiconal and Experimental field Cotaxtla in the state of Veracruz under seasonal conditions, during the spring summer 2010 cycle. The genotypes used were: H-520, H-564C, H-561, H-565, H-518, HEA1-17, (LPSC7F64-2-6-2-2-BBB/CML495)CML494, (CLG2312/CML495)CML494, (CML269/CML264)CML494. Based on the economic indicators analyzed in this paper, it was concluded that the use of certified seed could increase as long as the maize materials being evaluated present high yields and even though the cost of the seed would be very high. high, these would be justified and preferred by high productivity rates of new maize materials, which would respond to the expectations of corn producers.
Keywords: economic estimation; prices; productivity